HARTLEY AMPLITUDE MODULATION - Kokhanov, A.B.; Startsev, V.I.; Yemelianov, S.V.; Dereviagin, Y.V.; Pascu, D.G.; Barabanjv, N. (Sworld-Us Conference proceedings, 2023)
A new type of modulation has been developed - Hartley amplitude modulation(AMH), which is distinguished by the presence of two orthogonal components of the amplitude- modulated signal, which allows increasing the efficiency of AMX up to 90% compar